Energy Management in Solar Powered WLAN Mesh Nodes Using Online Meteorological Data - Sayegh, A.A.; Todd, T.D. (2007 IEEE International Conference on Communications, 2007)
Solar powered WLAN mesh nodes are assigned a solar panel and battery size based on power consumption profiles. If future loading exceeds the design target, then a node may not be able to achieve the outage performance for which it was configured. To prevent this from happening, forced power saving can be used to reduce node power consumption to acceptable levels. However, forced power saving generates a deficit in offered capacity which should be minimized as much as possible. In this paper we first formulate this as a non-linear control problem. An efficient linear programming approximation is then defined and solved based on an offline optimization where future solar insolation is known in advance. This provides a bound on the performance of any real control algorithm. We show that the LP solution is accurate in that it comes very close to achieving a no-control capacity deficit lower bound. A control algorithm is then proposed whose operation uses dynamic access to publicly available on-line meteorological data. The proposed approach uses this on-line data but could also benefit from on-line weather forecasting. Our results show that the proposed algorithm minimizes node outage and performs favorably compared to the offline and no-control lower bounds.